Prenatal and Early Life Fructose, Fructose-Containing Beverages, and Midchildhood Asthma - Wright, Lakiea S. (Ann Am Thorac Soc, 2018)
Rationale: Cross-sectional studies have linked intake of high-fructose corn syrup–sweetened beverages with asthma in schoolchildren. Objectives: To examine associations of maternal prenatal and early childhood intake of sugar-sweetened beverages and fructose with current asthma in midchildhood (median age, 7.7 yr). Methods: We assessed maternal pregnancy (first- and second-trimester average) and child (median age, 3.3 yr) intake of sugar-sweetened beverages and total fructose using food frequency questionnaires in 1,068 mother–child pairs from Project Viva, a prospective prebirth cohort. In a multivariable analysis, we examined associations of quartiles of maternal and child sugar-sweetened beverage, juice, and total fructose intake with child current asthma in midchildhood, assessed by questionnaire as ever having doctor-diagnosed asthma plus taking asthma medications or reporting wheezing in the past 12 months. Results: Higher maternal pregnancy sugar-sweetened beverage consumption (mean, 0.6 servings/d; range, 0–5) was associated with younger maternal age, nonwhite race/ethnicity, lower education and income, and higher prepregnancy body mass index. Adjusting for prepregnancy body mass index and other covariates, comparing quartile 4 with quartile 1, higher maternal pregnancy intake of sugar-sweetened beverages (odds ratio, 1.70; 95% confidence interval, 1.08–2.67) and total fructose (odds ratio, 1.58; 95% confidence interval, 0.98–2.53) were associated with greater odds of midchildhood current asthma (prevalence, 19%). Higher early childhood fructose intake (quartile 4 vs. quartile 1) was also associated with midchildhood current asthma in models adjusted for maternal sugar-sweetened beverages (odds ratio, 1.79; 95% confidence interval, 1.07–2.97) and after additional adjustment for midchildhood body mass index z-score (odds ratio, 1.77; 95% confidence interval, 1.06–2.95). Conclusions: Higher sugar-sweetened beverage and fructose intake during pregnancy and in early childhood was associated with childhood asthma development independent of adiposity.